Is a biological weapons arms race on the horizon: impact of scientific advances and strategic competition? - Glenn A. Cross; W. Seth Carus (Frontiers in Political Science, 2025)
This article considers the impact of advances in the biological sciences and related fields on the international system by considering the prospects that such developments will induce countries to adopt biological weapons and spark a biological weapons arms race. As such, it considers the relative importance of technological factors compared with other considerations (such as military utility and bureaucratic factors) in determining weapons system adoption.